Negara Islam Indonesia: Konsepsi Shajarah Tayyibah dalam Konstruk Negara Islam - Syofyan Hadi (JOURNAL OF QUR'AN AND HADITH STUDIES, 2013)
This article aims to prove that the interpretation of the verses of the Qur’an by using a rational approach to the political vision has a tendency to release an understanding of the text from its real context. This often makes an interpretation of these verses that are interpreted to justify and legalize the ideology that is being held. Based on the study of the works of supporters and leaders of the Negara Islam Indonesia (NII), this study proves that their interpretation is so far detached from the historical context of the Qur’an. More than once, the article insists, one verse is interpreted too far to legalize their aspiration without giving any reference to the traditions which are related to the context of the Qur’an, and the opinions of the previous ‘ulama’ and interpreters of the Qur’an, who are considered more authoritative in giving an interpretation to the verses of the Qur’an.